Introducing the Camry Electronic Hand Dynamometer EH101 as a Functional Strength Measurement Tool among Healthy Teenagers in Jakarta, Indonesia - Nury Nusdwinuringtyas; Ni Luh Made Murniasih Jayanthi; Endang Ernandini; Peggy Sunaryo; Jonathan Alvin Wiryaputra (Perkumpulan Kedokteran Militer, 2024)
Hand grip strength (HGS) is correlated with activities of daily living (ADL) and is intricately related to lung function. The American College of Sports Medicine recommends incorporating hand grip strength tests as a component of musculoskeletal fitness assessment for children. The hydraulic Jamar dynamometer, developed by Bechtol in 1954, is the most widely used tool among clinicians for measuring HGS. Currently, the widely available HGS measurement tool in Indonesia is the Camry electronic hand dynamometer EH101. This study aimed to introduce a new tool, known for its easy accessibility and affordability. An analytical observational design with a cross-sectional method. 19 males and 19 females, aged between 12–18 years, in one junior high school and one senior high school in Central Jakarta, who find inclucion criterias. There were differences of the results between both tools for all parameters. However, we detected consistency in term of the values of measurements. When the Jamar® measured a lower result than the other parameter, the Camry® would measure the same. A significant correlation between both values, as measured by Camry® and Jamar® (>0.7) that might be interpreted as a strong correlation of statistical significance. Camry EH101 had a significant correlation with Jamar, indicating consistency in measurements despite observed value gaps. While the Camry holds promise for use in Indonesia due to its affordability and accessibility, further investigation is warranted. It is recommended to calculate sensitivity and specificity of the Camry, considering its unique cut-off points for clinical application.